Rare case of bilateral carotid artery dissection presenting with Foix-Chavany-Marie syndrome. Issue 11 (30th November 2020) - Singh, Rajveer; Rebello, Alex; Prabhat, Nandita; Khurana, Dheeraj
Abstract : Carotid artery dissection is one of the most common causes of ischaemic stroke in young and middle-aged population. We report a case of bilateral carotid artery dissection presenting with opercular syndrome or Foix-Chavany-Marie syndrome. This 46-year-old obese and hypertensive man with a history of fall from bike 1 week prior, presented with sudden onset of anarthria, dysphagia and deviation of angle of mouth. His speech and dysphagia gradually improved over 10 days to normal, but he developed pseudobulbar affect and difficulty in calculations 4 weeks later. MRI showed acute infarcts in bilateral operculum. CT angiography showed dissection in bilateral cervical ICAs. He was managed conservatively with oral anticoagulation, given for 6 months. Probability of dissection must be considered in patients with a history of trauma or falls developing focal neurological deficits. To our knowledge, this is the first case report of bilateral ICA dissection presenting with Foix-Chavany-Marie syndrome.